Potensi Antibakterial Bakteri Asam Laktat dari Peda, Jambal Roti, dan Bekasam - Ninoek Indriati; Indriarto P. Danan Setiawan; Yulneriwarni Yulneriwarni (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Isolation of lactic acid bacteria from fermented fish products, peda, jambal roti and bekasam were carried out. Antibacterial activity of lactic acid bacteria was tested using well diffusion method against Escherichia coli, Bacillus cereus, Pseudomonas aeruginosa and Staphylococcus aureus. Twelve isolates of lactic acid bacteria had been isolated. Results showed that isolate A2 from peda was able to inhibit the growth of the 4 testing bacteria with inhibition zones of 6.7 mm for E. coli; 7.3 mm for P. aeruginosa; 8.3 mm for S. aureus and 10.0 mm for B. cereus. Isolate B5 from jambal roti had inhibition zones 11.6 mm for E. coli; 6.0 mm for P. aeruginosa ; 7.3 mm for S. aureus and 13.3 mm for B. cereus ; while isolate C6 from bekasam had inhibitor zones 7.7 mm for E. coli; 6.0 for P. aeruginosa; 8.0 mm for S. aureus and 9.3 mm for B. cereus.